Outcomes of Treatment in Patients with Severe Postmenopausal Osteoporosis: The Effects of Teriparatide Treatment on Bone Mineral Density, Back Pain and Biochemical Parameters - Tuba Nazlıgül; İlknur Aktaş; Feyza Ünlü Özkan; Pınar Akpınar (Galenos Yayinevi, 2020)
Objective:The aim of this study was to determine the effects of teriparatide treatment on bone mineral density (BMD), back pain, and biochemical parameters in patients with severe postmenopausal osteoporosis.Materials and Methods:The study included 13 patients with severe postmenopausal osteoporosis who were followed up at our osteoporosis outpatient clinic and completed treatment or currently undergoing treatment with subcutaneous 20 μq/day teriparatide. Patients were retrospectively evaluated before and after treatment with regards to BMD, biochemical parameters, and severity of back pain.Results:When the pre and post treatment values of the patients included in the study were compared, there was a statistically significant improvement in the BMD and severity of back pain after treatment (p<0.05), while the biochemical parameters did not differ significantly (p>0.05).Conclusion:In patients with severe postmenopausal osteoporosis, teriparatide therapy is seemed to be an effective treatment choice by improving the BMD values and reducing the back pain.